Hypoxia Delays Oligodendrocyte Progenitor Cell Migration and Myelin Formation by Suppressing Bmp2b Signaling in Larval Zebrafish - Yang, Lei-qing; Chen, Min; Zhang, Jun-long; Ren, Da-long; Hu, Bing (Frontiers in Cellular Neuroscience, 2018)
Hypoxia in newborns tends to result in developmental deficiencies in the white matter of the brain. As previous studies of the effects of hypoxia on neuronal development in rodents and human infants have been unable to use in vivo imaging, insight into the dynamic development of oligodendrocytes in the central nervous system under hypoxia is limited. Here, we developed a visual model to study oligodendrocyte development using sublethal postnatal hypoxia in zebrafish larvae. We observed that hypoxia significantly suppressed oligodendrocyte progenitor cell migration towards the dorsum using in vivo imaging. Further, we found that hypoxia affected myelination, as indicated by thinner myelin sheaths and by a downregulation of myelin basic protein expression. Bmp2b protein expression was also significantly downregulated following hypoxia onset. Using gain of function and loss of function experiments, we demonstrated that the Bmp2b protein was associated with the regulation of oligodendrocyte development. Thus, our work provides a visual hypoxia model within which to observe oligodendrocyte development in vivo, and reveals the underlying mechanisms involved in these processes.